Agalsidase alfa in pediatric patients with Fabry disease: a 6.5-year open-label follow-up study - Schiffmann, Raphael (Orphanet J Rare Dis, 2014)
BACKGROUND: Signs and symptoms of the X-linked disorder, Fabry disease (FD), can occur early during childhood with heterogeneous clinical manifestations including potential cardiac and renal dysfunction. Several studies support the efficacy of the enzyme replacement therapy (ERT) agalsidase alfa, in adults with FD, though published data on the long-term safety and efficacy of agalsidase alfa in children are limited. As early treatment with ERT has the potential to reduce complications arising from disease progression, children in particular could benefit. The objective of this study was to evaluate the safety and efficacy of long-term agalsidase alfa ERT in children with FD. METHODS: TKT029 was a 6.5-year open-label, multicenter, extension study of children who completed TKT023 (26-week, open-label, every-other-week, intravenous 0.2 mg/kg agalsidase alfa). TKT029 was divided into two phases (before and after an agalsidase alfa manufacturing process change); only patients who participated in both phases were included in the analysis. Primary endpoints included safety, tolerability, and heart rate variability (HRV). Additional efficacy parameters included left ventricular mass index (LVMI), estimated glomerular filtration rate (eGFR), and plasma/urine globotriaosylceramide (Gb(3)). RESULTS: Eleven patients participated (phase 1 baseline median [range] age: 10.8 [8.6–17.3] years; 10 [90.9%] males). During TKT029 (6.5 years), all patients experienced ≥1 treatment-emergent adverse event (AE); eight patients had ≥1 possibly/probably drug-related AE. Six patients experienced infusion-related AEs, but none discontinued due to AEs. Eight serious AEs arose (two patients); none were deemed drug-related. No deaths occurred. Three patients developed anti-agalsidase alfa antibodies, with IgG antibodies in one patient that were agalsidase alfa neutralizing, but without apparent clinical impact. Renal (eGFR) endpoints remained generally in normal range. Cardiac endpoints remained stable within normal range for LVMI and a trend towards improved HRV, although some patients experienced a reduction in heart rate. Plasma and urinary Gb(3) reductions were maintained. CONCLUSIONS: TKT029 represents the longest assessment of ERT in children with FD in a clinical trial setting. Overall, agalsidase alfa was well tolerated and demonstrated a stabilizing clinical effect. Agalsidase alfa may be a useful clinical therapeutic option for long-term treatment initiated during childhood in patients with FD. TRIAL REGISTRATION: http://ClinicalTrials.gov identifier NCT00084084. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13023-014-0169-6) contains supplementary material, which is available to authorized users.